Durable versus biodegradable polymer drug-eluting stents in all-comers - Pascal Meier; Stéphane Cook; MARIO TOGNI; Serban Puricel; Diego Arroyo; Thierry Witzig; Alain Witzig (Open Heart)
Background Drug-eluting stents (DESs) have become the gold standard of coronary angioplasty since their inception in 2002. Biodegradable polymer DESs (BP-DESs) have been postulated to be superior to durable polymer DESs (DP-DESs) due to their more biocompatible polymer. To date, no study has shown the superiority of one type of polymer compared with the other. We aimed to compare outcomes between a broad range of second-generation DP-DES and BP-DES in an all-comer population.Methods We analysed data from 2824 patients who underwent percutaneous coronary intervention (PCI) with BP-DES or DP-DES in the Cardio-FR database. Of these, 2079 (1286 DP-DES and 793 BP-DES) met the inclusion and exclusion criteria and completed a 2-year follow-up: The primary outcome was the device-oriented composite endpoint (DOCE) of cardiac death, non-fatal target vessel myocardial infarction and target lesion revascularisation.Results Mean age was 67 years, with 75% male. Despite the DP-DES group exhibiting significantly higher rates of risk factors, such as arterial hypertension (63.1% vs 57.5%, p=0.010), a greater average number of stents implanted per patient (1.72±0.92 vs 1.63±0.84, p=0.040), more acute coronary syndrome (ACS) (55.1% vs 50.2%, p=0.031) and a higher rate of post-dilatation (42.2% vs 35.2%, p<0.001), the rate of acute stent thrombosis (ST) was significantly lower than in the BP-DES group (HR 0.240, 95% CI 0.075 to 0.766; p=0.016). This difference remained significant even after adjusting for covariates using a Cox proportional hazards model and performing a win ratio analysis (4.09, 95% CI 1.28 to 13.09; p=0.018). Despite this increased rate of acute ST, there was no difference in DOCE (12.1% vs 14.5%, OR 1.218, 95% CI 0.926 to 1.600; p=0.158) between the two groups up to 2 years.Conclusion Clinical follow-up up to 2 years shows similar outcomes between BP-DES and DP-DES. The rate of acute ST is higher in patients with BP-DES.